Investment of financially distressed firms: The role of trade credit - Annalisa Ferrando; Marcin Wolski (European Investment Bank (EIB), 2018)
We study the relationship between net trade credit and firms' investment levels, focusing on financially distressed firms. First, we introduce a theoretical model to predict the role played by net trade credit as a coordination device differentiating firms by their degree of financial distress. Then, we test these predictions by using a large panel of more than 10 million firms in 23 EU countries over the period 2004-2014. Our main result is that, whereby net trade credit has an overall negative impact on capital formation due to liquidity effects, the effect is less pronounced for firms that are in financial difficulties. The main explanation is that through capital expenditures distressed companies try to maintain vital business relations with their customers in order to participate in the final profits via trade credit repayments.
Keywords: E22; G20; G30; 330; trade credit; investment; financial constraints; distressed firms